2020
DOI: 10.1002/jsfa.10664
|View full text |Cite
|
Sign up to set email alerts
|

Enriched cereal bars with wine fermentation biomass

Abstract: BACKGROUND: Cereal bars are a sweet-tasting, nutritious, and enjoyable source of vitamins, minerals, and fiber. Ingredients can be added to the formulation to improve certain characteristics, such as protein content. Some of these ingredients are derived from yeast from fermentation processes. This study aimed to add value to the residue resulting from the wine fermentation process (wine lees) by applying it in the formulation of cereal bars. RESULTS: Three formulations of cereal bars with different concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 23 publications
1
10
0
2
Order By: Relevance
“…As a result, AB presented a high quantity of ashes concerning NB. Other studies also reported the same behavior 14,31 . Results for protein showed a significant difference between the samples with an unexpected decrease for AB, but the result can be explained by the chemical autolysis.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…As a result, AB presented a high quantity of ashes concerning NB. Other studies also reported the same behavior 14,31 . Results for protein showed a significant difference between the samples with an unexpected decrease for AB, but the result can be explained by the chemical autolysis.…”
Section: Resultssupporting
confidence: 63%
“…Besides, during the storage of burger occurred the inhibition of psychotropic aerobic bacteria and enterobacteria. Borges et al 14 found an increase in the protein content of cereal bars using wine lees as an ingredient. Another study made by Sharma et al 15 discovered that the addition of wine lees in ice cream has improved the antioxidant properties and increased the phenols and anthocyanins content.…”
Section: Introductionmentioning
confidence: 98%
“…As a result of the growing global interest in the relationship between nutrition and health, recent studies focused on the development of innovative food products [70,87]. Some researchers have analyzed the possibility of integrating agro-food by-products to produce foods improved by a nutritional point of view.…”
Section: Production Of High-added Value Foodsmentioning
confidence: 99%
“…For this purpose, Borges et al [70] added wine lees to produce cereal bars. Wine lees represent a precious by-product linked to the presence of insoluble carbohydrates (from cellulosic and hemicellulosic fractions), phenolic compounds, and lignin, but especially proteins, which make wine lees nutritionally very rich [70,73].…”
Section: Production Of High-added Value Foodsmentioning
confidence: 99%
“…No entanto Maia et al (2021) obtiveram valores de umidade (9,30-10,32 %) e atividade de água (0,523-0,557) próximas ao encontrado no presente estudo ao aplicarem proteínas de leguminosas (ervilha, feijão caupi e feijão mangalô). Da mesma forma, Borges et al (2021) encontraram valores de umidade entre 11-12 % e atividade de água entre 0,554 e 0,571 para barras de cereais enriquecidas com biomassa de fermentação de vinho. A curva de contorno (Figura 9) indicou que menores valores de umidade foram obtidos com os menores níveis de resíduo de mosturação e da razão gelatina:água.…”
Section: Atividade De áGua E Umidadeunclassified